Jannis Kounellis - Senza titolo (Nabucco) - Lonardelli, Luigia 1982- (MAXXI, 2024)
Published on the occasion of the Jannis Kounellis exhibition, the leporello brings together a short curatorial text, images of the installation at MAXXI and photographs of the work Senza titolo [Nabucco] on the occasion of the exhibition Vitalità del negativo dell’arte italiana 1960-70, held in Rome in 1970. The protagonists of the leporello are the images, the historical shots by Claudio Abate, Cristina Ghergo, Ugo Mulas and Massimo Piersanti, and the colour photographs documenting the exhibition’s staging at MAXXI. The hardback cover and translucent paper envelope give the leporello a precious dimension that transforms the publication into a collector’s item for enthusiasts
Impressum: "Jannis Kounellis. Notte", MAXXI-Museo nazionale delle arti del XXI secolo, 14 dicembre 2023 - 26 maggio 2024
Keywords: Kounellis, Jannis -- 1936-2017; Ausstellungskatalog -- Museo nazionale delle arti del XXI secolo -- 14.12.2023-26.05.2024 -- Rom; Bildband